Computational Thinking Skills in 21st Century Mathematics Learning - Mendrofa, Netti Kariani (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Computational thinking skills are a crucial mental skill in the 21st century, enabling individuals to solve problems, understand data, and make decisions with a structured and computational-based approach. Integrating computational thinking skills in mathematics learning has an important role in preparing students to become skilled in thinking computationally in the 21st century. The method used in this research is library research in which relevant data are collected from sources such as books, dictionaries, journals, magazines, and others without the need to conduct direct investigations in the field. Applying computational thinking in mathematics learning will foster skills such as decomposition (breaking down a problem into manageable parts), pattern recognition, abstraction, and algorithm design as well as developing analytical and abstract thinking skills.